PENINGKATAN KETERAMPILAN MENULIS DESKRIPSI DENGAN PENERAPAN METODE QUANTUM LEARNING PADA SISWA KELAS IV SDN JEMUR WONOSARI III/526 SURABAYA - Suprobowati Suprobowati (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2019)
The application of quantum learning method as a means to improve the ability to write description in fourth grade students of SDN Jemur Wonosari III/526 Surabaya  . After the researchers explain about the application of quantum learning methods to teachers and their advantages, the teacher also agreed to apply the method of quantum learning in learning to write a description. Through the method of quantum learning is expected to foster interest and activity of students in learning to write a description. Such interest and interest will foster students 'enjoyment in learning that will ultimately improve students' learning abilities and learning outcomes. Therefore this research entitled "Improvement of Descriptive Writing Skill with Implementation of Quantum Learning Method on Grade IV Students of SDN Jemur Wonosari III/526 Surabaya  .The application of quantum learning method can improve the learning process of writing description in fourth grade students of SDN Jemur Wonosari III/526 Surabaya  . This is evidenced by the increased learning process, which includes: (a) increasing student activeness when following apersepsi. It can be seen from the increase of student activeness when following apersepsi at each cycle. In the first cycle students activeness when following apersepsi by 72%, on the second cycle of 92%; (b) increased activity and attention during learning. This is evidenced by the increased activity of students in responding to the stimulus provided by the teacher (asking, answering, responding, naming) and attention at the time of learning in each cycle. Cycle I active students follow the learning activities by 72%. In the next cycle the activity of students during the learning activities has increased significantly. The increase is 80% in cycle II; (c) the increased motivation and interest of students in following the learning of writing the description. This seems apada sincerity of students while doing the task and enthusiasm and spirit of students while following the learning activities. In the first cycle students who seem interested and motivated as much as 64%, in the next cycle increased to 81% in cycle II.